Menstrual cups and sanitary pads to reduce school attrition, and sexually transmitted and reproductive tract infections: a cluster randomised controlled feasibility study in rural Western Kenya. Issue 11 (23rd November 2016) - Phillips-Howard, Penelope A; Nyothach, Elizabeth; ter Kuile, Feiko O; Omoto, Jackton; Wang, Duolao; Zeh, Clement; Onyango, Clayton; Mason, Linda; Alexander, Kelly T; Odhiambo, Frank O; Eleveld, Alie; Mohammed, Aisha; et al.
Abstract : Objectives: Conduct a feasibility study on the effect of menstrual hygiene on schoolgirls' school and health (reproductive/sexual) outcomes. Design: 3-arm single-site open cluster randomised controlled pilot study. Setting: 30 primary schools in rural western Kenya, within a Health and Demographic Surveillance System. Participants: Primary schoolgirls 14–16 years, experienced 3 menses, no precluding disability, and resident in the study area. Interventions: 1 insertable menstrual cup, or monthly sanitary pads, against 'usual practice' control. All participants received puberty education preintervention, and hand wash soap during intervention. Schools received hand wash soap. Primary and secondary outcome measures: Primary: school attrition (drop-out, absence); secondary: sexually transmitted infection (STI) ( Trichomonas vaginalis, Chlamydia trachomatis, Neisseria gonorrhoea ), reproductive tract infection (RTI) (bacterial vaginosis, Candida albicans ); safety: toxic shock syndrome, vaginal Staphylococcus aureus . Results: Of 751 girls enrolled 644 were followed-up for a median of 10.9 months. Cups or pads did not reduce school dropout risk (control=8.0%, cups=11.2%, pads=10.2%). Self-reported absence was rarely reported and not assessable. Prevalence of STIs in the end-of-study survey among controls was 7.7% versus 4.2% in the cups arm (adjusted prevalence ratio (aPR) 0.48, 0.24 to 0.96, p=0.039), 4.5% with pads (aPR=0.62; 0.37 to 1.03, p=0.063), and 4.3% with cups and pads pooled (aPR=0.54, 0.34 to 0.87, p=0.012). RTI prevalence was 21.5%, 28.5% and 26.9% among cup, pad and control arms, 71% of which were bacterial vaginosis, with a prevalence of 14.6%, 19.8% and 20.5%, per arm, respectively. Bacterial vaginosis was less prevalent in the cups (12.9%) compared with pads (20.3%, aPR=0.65, 0.44 to 0.97, p=0.034) and control (19.2%, aPR=0.67, 0.43 to 1.04, p=0.075) arm girls enrolled for 9 months or longer. No adverse events were identified. Conclusions: Provision of menstrual cups and sanitary pads for ∼1 school-year was associated with a lower STI risk, and cups with a lower bacterial vaginosis risk, but there was no association with school dropout. A large-scale trial on menstrual cups is warranted. Trial registration: ISRCTN17486946 ; Results